2017
DOI: 10.1038/bdjopen.2017.12
|View full text |Cite
|
Sign up to set email alerts
|

Clinical performance of the near-infrared imaging system VistaCam iX Proxi for detection of approximal enamel lesions

Abstract: Objectives/Aims:Apart from the visual detection of caries, X-rays can be taken for detection of approximal lesions. The Proxi head of VistaCam iX intraoral camera system uses near-infrared light (NIR) to enable caries detection in approximal surfaces. The aim of this study was to evaluate the performance of the NIR for the detection of approximal enamel lesions by comparison with radiographic findings.Materials and methods:One hundred ninety-three approximal surfaces from 18 patients were examined visually and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 27 publications
2
35
0
Order By: Relevance
“…Initial in-vitro studies using ICDAS-II for detection of occlusal lesions showed lower overall performance of ICDAS-II (AUC between 0.73-0.88) (Jablonski-Momeni et al 2008) and (Rodrigues et al 2008). Later studies showed an increase of ICDAS-II performance, sensitivity, and specificity values which might be explained by the enhanced training in this system (Jablonski-Momeni et al 2017).…”
Section: Discussionmentioning
confidence: 98%
“…Initial in-vitro studies using ICDAS-II for detection of occlusal lesions showed lower overall performance of ICDAS-II (AUC between 0.73-0.88) (Jablonski-Momeni et al 2008) and (Rodrigues et al 2008). Later studies showed an increase of ICDAS-II performance, sensitivity, and specificity values which might be explained by the enhanced training in this system (Jablonski-Momeni et al 2017).…”
Section: Discussionmentioning
confidence: 98%
“…Although not directly compared, commercial NIR‐camera‐based dental imaging systems use wavelengths below 900 nm so that inexpensive small silicon‐based cameras can be used. However, these wavelengths have 10 times higher optical scattering coefficient than 1200–1800 nm which may limit its imaging depth and diagnostic accuracy . Current 1200–1800‐nm NIR imaging requires InGaAs‐based pixel‐array cameras which are bulky and expensive .…”
Section: Discussionmentioning
confidence: 99%
“…However, moisture or saliva contamination has not affected the scores. Jablonski-Momeni et al compared near-infrared imaging system (VistaCam iX Proxi) and conventional digital radiographs for the diagnosis of proximal enamel lesions and found that there was moderate agreement between the methods and found no significant difference 18. A recent systematic review on LIF with Soprolife IOC has concluded that there was no clear evidence on the detection of occlusal caries lesions and recommended future studies 19…”
Section: Applications Of Iocmentioning
confidence: 99%